Культурний трансфер – нова методологія компаративістики - Сиваченко, Г.М. (Слово і Час, 2019)
У статті подано огляд тенденцій у розвитку сучасного підходу в аналізі літературних і культурних явищ. Теорія культурного трансферу одночасно вивчає не лише кілька культурних і національних просторів, а й вкраплення, трансформації, які при будь-якому зближенні культур виявляються як у впливовій культурі, так і в культурі-сприймачі. Вивчення периферії культурного простору, тобто тих зв'язків, які кожна культура через необхідність підтримує із чужим культурним простором, стає пріоритетним, демонструючи в національному явищі складний сплав різних культур і взаємовпливів. До об'єктів культурного трансферу належить також історія перекладу. Студії перекладних текстів дедалі більше перетинаються з простором суміжних гуманітарних дисциплін. Об'єктом розгляду “культурологічного перекладознавства” стає текст у системі літературних і позалітературних смислів у межах вихідної культури і культури-приймача. A theory of cultural transfer was the branch of comparative literary criticism, although this theory declared its sharp opposition against the mentioned tradition of study. The comparative studies in humanities are based on the ideas of specificity of every culture, even when one deals with the infl uence of one culture on another. Instead of this approach, the theory of cultural transfer promotes not only a simultaneous study of several cultural and national spaces but also a research on disseminations and transformations that appear at any rapprochement between cultures both in an influential culture and in a perceiving one. Consequently, it is not the binary opposition that must be taken into account in cultural transfer but two cultures, one of which is necessarily comprehended as a culture-recipient, although the whole scheme is much more complicated. Any transition from one cultural space into another easily may cause some transformation. Other ‘new element’ in the theory of cultural transfer is positioning the study of a cultural space periphery, i. e. connections with alien cultural space that every culture necessarily supports, in a center. This approach demonstrates that any phenomenon, no matter how specifically national it may be, actually is a complicated alloy of different cultures and influences. The objects of cultural transfer include the history of translation. Another priority direction is a comparative study of the national forms of comparativism related to the history of intellectual and spiritual relations between different countries and nations. During the transfer from one cultural situation into another any object gets into another context and acquires a new meaning. As focus of attention of a theory and studies of translation was shifting to the context of creation, operation and perception of translations, the research on the translated texts increasingly crossed the boundaries of the related disciplines that enabled learning this context – sociology, comparative studies, economics, history, cultural studies. The scholars aim to indicate the ways of manipulating the readers via translation, to explicate interests and values brought with every translation, to show how it forms the culture-receiver and values of society. The most attention is paid to the issues of ideology, economy and politics, the problems of ethnic responsibility of the translator. The object of cultural translation studies is the text in the system of literary and extra-literary meanings within the initial and receiving cultures. Cultural theory of translation raises the question of cultural prestige of the selected texts and determines the basis of this selection, the principles of forming and changing their status. One may focus also on the role of the commentator as an intermediary between the translator of the text and the readers to whom the translator wants to make his way through.